2007
DOI: 10.1007/s00280-007-0538-0
|View full text |Cite
|
Sign up to set email alerts
|

Mebendazole inhibits growth of human adrenocortical carcinoma cell lines implanted in nude mice

Abstract: Adrenocortical carcinoma is a rare tumor of the adrenal gland which requires new therapeutic approaches as its early diagnosis is difficult and prognosis poor despite therapies used. Recently, mebendazole has been proved to be effective against different cancers. The aim of our study was to evaluate whether mebendazole may result therapeutically useful in the treatment of human adrenocortical carcinoma. We analyzed the effect of mebendazole on human adrenocortical carcinoma cells in vitro and after implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 8 publications
4
68
0
Order By: Relevance
“…Benzimidazoles, specifically mebendazole and albendazole, have shown in vivo antitumor activity against a range of cancers, including hepatocellular, lung, and adrenocortical carcinoma (5,6,21). Mebendazole is more suited for clinical study than other benzimidazoles identified in our screen given its status as a marketed drug, its oral availability, and its favorable safety profile in long-term treatment regimens (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Benzimidazoles, specifically mebendazole and albendazole, have shown in vivo antitumor activity against a range of cancers, including hepatocellular, lung, and adrenocortical carcinoma (5,6,21). Mebendazole is more suited for clinical study than other benzimidazoles identified in our screen given its status as a marketed drug, its oral availability, and its favorable safety profile in long-term treatment regimens (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, further assessment of mebendazole using an in vivo model of chemoresistant melanoma is a prerequisite before embarking on human studies. In light of promising in vivo studies showing the remarkable tumor growth inhibition of mebendazole in lung and adrenocortical carcinoma, it is reasonable to suggest that mebendazole will also be effective against malignant melanoma (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The benzamidazole mebendazole significantly inhibited growth of adrenocortical carcinoma cells, both in vitro and in vivo, the effects being due to induction of apoptosis [19]. Moreover, mebendazole inhibited invasion and migration of cancer cells in vitro, and formation of metastases in vivo in experimental animals.…”
Section: Anticancer Activity Of Mebendazolementioning
confidence: 97%